Reasons for Child trafficking with special reference to Chennai - Dhanusreeharini, S. (International Journal of Psychosocial Rehabilitation, 2020)
Child trafficking is one of the forms of human trafficking. Trafficking in ladies and youngsters is one of the most exceedingly awful misuses of human rights. Be that as it may, it is exceptionally hard to appraise the size of the marvel as trafficking is firmly identified with youngster work, fortified work, tyke marriage, seizing and kidnapping and prostitution despite the fact that these wonders can exist likewise free of trafficking. The objective of the study is to understand about the existence of child trafficking with regard to area and to identify the reason for child trafficking. Survey has been taken through convenient sampling method to validate this research. 1480 samples were collected. This paper has endeavored to break down the nature, causes, modes and volume of trafficking in a nation that has as of late turned into an easy prey in the South Asian locale for trafficking in people. India has neglected to conform to certain universal models to battle the wrongdoing. The paper features the need to build up a multidimensional approach and concentrates consideration on basic components of trafficking for prescribing important stratagems to counter the social malevolence